Endothelial Atg7 Deficiency Ameliorates Acute Cerebral Injury Induced by Ischemia/Reperfusion - Wang, Hui-Jie; Wei, Jia-Yi; Liu, Dong-Xin; Zhuang, Shi-Fang; Li, Yuan; Liu, Hui; Ban, Meng; Fang, Wen-Gang; Cao, Liu; Zhao, Wei-Dong; Chen, Yu-Hua (Frontiers in Neurology, 2018)
Ischemic strokes often result in cerebral injury due to ischemia/reperfusion (I/R). Although the local inflammatory responses are known to play a primary role in the brain I/R injury, the underlying mechanism remains unclear. In the current study, we investigated the effect of brain endothelial Atg7 (autophagy related 7) depletion in the acute brain injury induced by ischemia and reperfusion. Endothelial knockout of Atg7 in mice (Atg7 eKO) was found to significantly attenuate both the infarct volume and the neurological defects induced by I/R when compared to the controls. In fact, brain inflammatory responses induced by I/R were alleviated by the Atg7 eKO. Furthermore, an increased expression of pro-inflammatory cytokines, including IL-1β, IL-6, IL-8 and TNF-α, was observed in brain endothelial cells in response to oxygen/glucose depletion/reoxygenation, which was decreased by the shRNA-mediated Atg7 knockdown. Interestingly, Atg7 knockdown reduced IKKβ phosphorylation, leading to NF-κB deactivation and downregulation of the pro-inflammatory cytokines mRNA levels. Further, Atg7 transcriptional regulation function is independent of its role in autophagy. Taken together, our results demonstrated that brain endothelial Atg7 contributes to brain damage during I/R by modulating the expression of pro-inflammatory cytokines. Depletion of Atg7 in brain endothelium has a neuroprotective effect against the ischemia/reperfusion-induced acute cerebral injury during stroke.